The chances and limitations of applying a CSR strategy in Polish enterprises - Codogni, Iwona (Annales. Etyka w Życiu Gospodarczym, 2019)
The topic of the article is the perspectives of CSR in Polish companies. The article contains a definition of corporate social responsibility, the state and dynamics of ethical reporting, and the factors that can influence the dynamics of CSR in Poland—both in a favorable and adverse way.